2008
DOI: 10.1080/08860220802359410
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Proanthocyanidin on Renal Ischemia/Reperfusion Injury

Abstract: NTRODUCTION Several natural products have been reported to have beneficial effects on ischemia/reperfusion (I/R) injury, particularly from a preventative perspective. Therefore, this study was designed to investigate the efficiency of proanthocyanidin (PA), a natural product derived from grape seed, on renal dysfunction and injury induced by I/R of rat kidney. MATERIALS AND METHODS Twenty‐four male Sprague‐Dawley rats were divided into three groups: sham‐operated, I/R, I/R+PA. Rats were given PA (100 mg/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 38 publications
3
33
0
1
Order By: Relevance
“…Efficacy of treatment was assessed by tissue level of malondialdehyde (MDA) using the method of Ohkawa et al, protein carbonyl content (PCC) using the method of Levine et al, superoxide dismutase (SOD) using the method of Sun et al, and glutathione peroxidase (GPx) using the method of Paglia and Valentine. [13,30,40] Nitrate and nitrite (NO x ) levels, end products of nitric oxide degradation, were measured using the method described by Miranda et al, as we described in our previous works. [13,30] …”
Section: Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of treatment was assessed by tissue level of malondialdehyde (MDA) using the method of Ohkawa et al, protein carbonyl content (PCC) using the method of Levine et al, superoxide dismutase (SOD) using the method of Sun et al, and glutathione peroxidase (GPx) using the method of Paglia and Valentine. [13,30,40] Nitrate and nitrite (NO x ) levels, end products of nitric oxide degradation, were measured using the method described by Miranda et al, as we described in our previous works. [13,30] …”
Section: Biochemical Analysismentioning
confidence: 99%
“…[7,15] Various in vivo studies have shown that NO biosynthesis and its action are closely related to the pathogenesis of renal I/R injury. In addition, it has been shown that selective or non-selective iNOS inhibitors prevent I/R injury in skeletal muscle, myocardial infarction, brain, liver, and kidney tissues, [13,[16][17][18][19][20][21] and that iNOS-knockout mice show reduced I/R injury in the kidney. [20] Melatonin is mainly secreted from pineal gland and a variety of non-pineal tissues and organs, including the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate plus nitrite (NO x ) levels, end products of nitric oxide degradation, were measured using the method described by Miranda et al, as we described in our previous works. [5,6] …”
Section: Biochemical Analysismentioning
confidence: 99%
“…[7] In our previous studies, we have shown that the inhibition of iNOS and scavenging of ONOO − reduced the damage in the kidneys subjected to renal I/R. [5,6] Studies have shown that ONOO ® induces cellular injury by activation of poly (ADP-ribose) polymerase (PARP) through damaging DNA. Deoxyribonucleic acid damage is repaired via the activity of several DNA repair enzymes, including PARP enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation